Retirement Portfolios Workbook : Theory, Construction, and Management - Zwecher, Michael J., 1957- (Wiley finance series., 2010)
A companion Workbook to the text Retirement Portfolios. Retirement is one of the most important parts of the financial planning process. Yet only two percent of financial advisors describe themselves as competent in retirement planning. Constructing a retirement portfolio is viewed as a difficult endeavor, and the demands facing financial advisors responsible for this task continue to grow. The pressures are particularly intense due to events such as the financial crisis and oncoming rush of retiring baby boomers. It is imperative that financial advisors be equipped and ready to create appropr.